Decoupling relationship between haze pollution and economic growth: A new decoupling index - Feng Dong; Jingyun Li; Xiaoyun Zhang; Jiao Zhu (Ecological Indicators, 2021)
Economic development is accompanied by the production of pollutants. Coordinating the relationship between economic development and haze pollution is of great significance to future development in China. Based on the original decoupling index (Tapio decoupling index), this study developed a new decoupling index that overcomes some of the original defects and highlights the trends to a better extent. It also analyzes the transformation relationship among the new decoupling index, the original decoupling index and the EKC curve. Firstly, we compared the changing trends of the two decoupling indexes and then derived the factors that influence the new and original decoupling indexes based on C-D-Kaya equation. Finally, we compared the factors influencing the two decoupling indexes from the perspective of decomposition analysis and measurement. The conclusions are as follows: (1) Based on the limit theory, the boundary point for relative decoupling and absolute decoupling derived from the original decoupling index can be used to determine the inflection point of the EKC curve. The new decoupling index can also reflect this property. At the inflection point of the EKC curve, the ratio of the new decoupling index of two adjacent periods satisfies equation (12), which is only related to GDP. (2) In 2003, the new decoupling index showed a downward trend, and the fluctuation was smaller than that of the original decoupling index. The original decoupling index is more sensitive to short-term policies than the new decoupling index, but the new decoupling index is more conducive to the comprehensive analysis of China’s decoupling trend. (3) After decomposing the new decoupling index and the original decoupling index, per capita GDP and the emission coefficient are the largest positive and negative driving forces, respectively. However, the trend of the contribution made by each factor was more obvious when the new decoupling index was used. The emission coefficient for Shandong made the largest negative contribution, and the per capita GDP for Shanxi made the greatest positive contribution. (4) The geographically and temporally weighted regression (GTWR) analysis showed that the fitting degree of the new decoupling index is much higher than that of the original decoupling index. The analysis of the influencing factors affecting the new decoupling index showed that there was temporal and spatial heterogeneity among the factors in east, middle, and west China, and there were significant differences in the impacts due to energy structure, energy intensity, technological progress, and urban population factors, respectively. These findings will significantly improve the formulation of efficient and pertinent policies for energy conservation and haze reduction.